Bahasa Inggris - Zakiyyah Salsabila; Asep Hardiyanto (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to explore and compare the teaching practicum experiences of Indonesian and Filipino student interns in secondary schools in the Philippines, with a focus on institutional support, challenges encountered, and the development of teaching competence. Employing a qualitative comparative design, data were collected through semi-structured interviews with Indonesian student interns participating in the SEA-Teacher Program who completed an international practicum, as well as Filipino pre-service teachers undertaking domestic practicum programs at Capiz State University. The interview data were analyzed using thematic analysis. The findings reveal that Indonesian participants primarily experienced challenges related to language confidence, intercultural communication, and adaptation to an ESL environment, whereas Filipino participants benefited more from sustained pedagogical mentoring and encountered challenges associated with classroom management and learner diversity. Despite these differences, both groups demonstrated adaptive teaching strategies and meaningful professional growth through reflective classroom experiences. Indonesian participants exhibited stronger development in intercultural awareness and professional identity, while Filipino participants demonstrated greater pedagogical refinement and instructional effectiveness. These findings highlight the influence of sociolinguistic context, institutional familiarity, and cross-cultural engagement on professional learning during teaching practicum. The study also emphasizes the importance of strengthening mentoring systems, intercultural preparation, and language readiness in international teaching internship programs.